Hubungan Cita Rasa Makanan Dan Konsumsi Makanan Dari Luar Rumah Sakit Dengan Sisa Makanan Biasa Pada Pasien Di Rumah Sakit Orthopedi Prof.Dr.R.Soeharso Surakarta - Nafies, Dian Ayu Ainun, Endang Nur Widyaningsih, SST.,M.Si.,Med (2016)
Introduction: Indicators of success in the implementation of nutrition service quality is the amount of food waste . There are several factors that can affect the food waste , among others, the taste of food and food from outside the hospital. According to the survey, the percentage of food waste s in the Orthopedic Hospital of Surakarta still have not reached the minimum service standards. Objective: The purpose of the research was to determine the correlation the taste of food and consumption of food from outside the hospital with the food waste of the regular food of patients in Soeharso Orthopaedic Hospital of Surakarta. Research Methods: The research used cross sectional design. The total subject were 35 patients class III, who got regular food which had qualification of inclusion and exclusion. Sampling is by using consequtive sampling. The taste of food and consumption of food from outside the hospital data were obtained by questionnaires, and food waste data were obtained by comstock form. Result: The taste of food, 62.9% of respondents said good, 65.7% of respondents often consumed food from outside the hospital. The average of food waste was domintaed by rice, that was 24.4%. The results of correlation test between the taste of food and food waste was (p=0.85), The consumption of food from outside the hospital and food waste was (p= 0.01). Conclusion: There was no correlation between the taste of food with food waste in the hospital. There was correlation between the consumption of food from outside the hospital with food waste in the hospital. Suggestion: Evaluation is needed to the consumption of food from outside the hospital in order to decrease the number of food waste that still exceeds the minimum service standards of the hospital.